Life history and point prevalence of low back pain in pre-professional and professional dancers - Swain, C. T. V.; Bradshaw, E. J.; Whyte, D. G.; Ekegren, C. L. (Physical Therapy in Sport, 2017)
Objectives: To investigate lifetime history and point prevalence of low back pain (LBP) in pre-professional and professional dancers and to identify any demographic or physical factors associated with LBP in dancers. Design: Cross-sectional study. Setting: One pre-professional ballet school, two pre-professional university dance programs, and a professional nationally touring ballet company. Participants: Male and female classical ballet and contemporary dancers aged 12 years old and above. Main outcome measures: Lifetime history and point prevalence of LBP. Results: A total of 110 (n ¼ 19 male) dancers (mean (SD) 17.8 (2.9) years old) participated in the study, which represented 50% of the population invited to participate. A 74% lifetime prevalence of LBP was reported by dancers. Point and 12 month prevalence were 24 and 64%, respectively. No significant association was observed between LBP and any demographic or physical variables. Conclusion: Pre-professional and professional dancers have an increased vulnerability to LBP. The development of LBP within this population is complex and may not be associated with individual factors measured in this study.